Wreck of Georgette, The - Chapman, Jean (Cleveland, Ohio : Modern Curriculum Press, 1987)
Last century, off the South-West coast of Western Australia, a small ship sprang a leak while battling heavy seas and gale-force winds.
Keywords: Ships -- Juvenile literature; Children stories